The Structure and Immune Regulatory Implications of the Ubiquitin-Like Tandem Domain Within an Avian 2’-5’ Oligoadenylate Synthetase-Like Protein - Shepard, Justin D.; Freitas, Brendan T.; Rodriguez, Sergio E.; Scholte, Florine E. M.; Baker, Kailee; Hutchison, Madelyn R.; Longo, Jaron E.; Miller, Holden C.; O’Boyle, Brady M.; Tandon, Aarushi; Zhao, Peng; Grimsey, Neil J.; et al. (Frontiers in Immunology, 2022)
Post-translational modification of host and viral proteins by ubiquitin and ubiquitin-like proteins plays a key role in a host’s ability to mount an effective immune response. Avian species lack a ubiquitin-like protein found in mammals and other non-avian reptiles; interferon stimulated gene product 15 (ISG15). ISG15 serves as a messenger molecule and can be conjugated to both host and viral proteins leading them to be stabilized, degraded, or sequestered. Structurally, ISG15 is comprised of a tandem ubiquitin-like domain (Ubl), which serves as the motif for post-translational modification. The 2’-5’ oligoadenylate synthetase-like proteins (OASL) also encode two Ubl domains in series near its C-terminus which binds OASL to retinoic acid inducible gene-I (RIG-I). This protein-protein interaction increases the sensitivity of RIG-I and results in an enhanced production of type 1 interferons and a robust immune response. Unlike human and other mammalian OASL homologues, avian OASLs terminate their tandem Ubl domains with the same LRLRGG motif found in ubiquitin and ISG15, a motif required for their conjugation to proteins. By investigating chicken OASL (chOASL), the evolutionary history of viruses with deubiquitinases can be explored and drivers of species specificity for these viruses may be uncovered. Here we show that the chOASL tandem Ubl domains shares structural characteristics with mammalian ISG15, and that chOASL can oligomerize and conjugate to itself. In addition, the ISG15-like features of avian OASLs and how they impact interactions with viral deubiquitinases and deISGylases are explored.